1970
DOI: 10.1677/joe.0.0470045
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Dorsal Tracts of the Spinal Cord and of the Mesencephalic and Thalamic Lemniscal System in the Milk-Ejection Reflex During Milking in the Ewe

Abstract: The milk-ejection reflex after different lesions of the sensory system was studied by mechanical milking of the ewe. Only animals with lesions which did not produce locomotor ataxia were investigated. Section of the dorsal tract of the spinal cord at different thoracic levels blocked the mi l k\x=req-\ ejection reflex. This was not due to postoperative shock, because the same type of lesion made at the sacral level was without effect. Moreover, unilateral section of this tract blocked the reflex when milking w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

1971
1971
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…Our findings are more in accord with previous observations in other species that milk ejection was not impaired by small bilateral lesions in the lateral hypothalamus (Averill, 1965), subthalamus, medial lemniscus, ventral postero-lateral nucleus, midbrain reticular formation and central grey (Richard, 1969;Richard et al 1970), and with the fact that large lesions in the mid-brain tegmentum (Richard, 1969) or the diencephalic periventricular region (Beyer & Mena, 1965) are required to prevent Fig. 8.…”
Section: Characterization Of Endogenous Oxytocin Releasesupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are more in accord with previous observations in other species that milk ejection was not impaired by small bilateral lesions in the lateral hypothalamus (Averill, 1965), subthalamus, medial lemniscus, ventral postero-lateral nucleus, midbrain reticular formation and central grey (Richard, 1969;Richard et al 1970), and with the fact that large lesions in the mid-brain tegmentum (Richard, 1969) or the diencephalic periventricular region (Beyer & Mena, 1965) are required to prevent Fig. 8.…”
Section: Characterization Of Endogenous Oxytocin Releasesupporting
confidence: 92%
“…DISCUSSION It has long been known that oxytocin as measured by the milk-ejection response can be released by electrical stimulation of both the brain-stem and forebrain (Andersson, 1951 ;Cross, 1961). This evidence for converging projections to the hypo¬ thalamic nuclei (PV and supraoptic) controlling oxytocin secretion has been con¬ firmed and extended (Holland, Woods & Aulsebrook, 1963;Tindal et al 1968Tindal et al , 1969Richard, Urban & Denamur, 1970) but there has been no firm agreement on the identity of the afferent pathways involved. For the mid-brain the most impressive studies have been those of Tindal et al (1968,1969) in the guinea-pig and rabbit.…”
Section: Characterization Of Endogenous Oxytocin Releasementioning
confidence: 99%
See 1 more Smart Citation
“…On no occasions in this, or in our previous studies have we observed changes in the background activity of neurosecretory cells which might be related to the sucking of individual young, and further, a detailed analysis of the sucking motions of both individual young and the litter has failed to reveal a change in the on-going sucking activity at the time of neurosecretory activation (Drewett, Statham & Wakerley, 1974 Richard et al 1970). Presumably the distending effect of the saline would stimulate intramammary mechanoreceptors (Cross & Findlay, 1969) and create an afferent barrage which, combined with the on-going stimulation provided by the pups, would open the proposed gate and trigger a neurosecretory response proportional to the incoming signal.…”
Section: Relationship Of Neurosecretory Activation To Oxytocin Releasementioning
confidence: 52%
“…A neural gate in the afferent limb of the milk ejection reflex could operate at any of several levels in the brain and spinal cord. Tindal (1971) has suggested that the suckling stimulus might be gated at a spinal level, whilst the findings of Richard, Urban & Denamur (1970) suggest that the transmission of stimuli from the mammary gland through extralemniscal fibres may be regulated by lemniscal co-laterals at a subthalamic level. Alternatively, the control might be exerted through inhibitory connexions at the level of the neurosecretory nuclei themselves.…”
Section: Relationship Of Neurosecretory Activation To Oxytocin Releasementioning
confidence: 99%